STUDI HIDROLOGI HUTAN KOTA KAMPUS UNIVERSITAS INDONESIA DEPO - Kusratmoko, E; Tambunan, M. P.; Sobirin, Sobirin (UI Scholars Hub, 2002)
Hydrological Study on the urban forest in Campus Area of the Indonesia University, Depok during September 2000 – February 2001 hydrological measurement of urban forest in Campus Area of the Indonesia University, Depok were carried out to identify the effect of land cover on the runoff generation processes. Seven observation station which are characteristised by differenced land cover were build to measure overland and sub surface fl ow. The result of data analysis showed that the grass and litter cover in urban forest fl oor played an important role as a control factor of overland fl ow and throughfl ow production, especially signifi cant during the convective rains. During this events the proportion of throughfall on this area which produced overland fl ow, varied between 5,3-7,2%, while on the area without the grass and litter cover, its about 12,5-18,9%. During December–February the overland fl ow was very high. This is probably closely related to the existence of the widespread saturation overland fl ow. Generally it was shown a very close relationship between throughfall and overlandfl ow on the area without the grass and litter cover. The effect of antecedent precipitation index on the overland and throughfl ow production was identifi ed on the location with grass cover and cultivated area and particularly signifi cant on the events with throughfall >40 mm.